2003
DOI: 10.1124/jpet.103.055905
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Spinal Muscarinic Receptors and Increased Antinociceptive Effect of Intrathecal Muscarine in Diabetic Rats

Abstract: Spinally administered muscarinic receptor agonists or acetylcholinesterase inhibitors produce effective pain relief. Intrathecal injection of a small dose of neostigmine produces a profound antiallodynic effect in rats with diabetic neuropathy. However, the mechanisms of increased antinociceptive effect of cholinergic agents on diabetic neuropathic pain are not clear. In the present study, we tested the hypothesis that spinal muscarinic receptors are up-regulated in diabetes. The withdrawal threshold of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Using mAChR subtype knockout mice, it has been shown that the M 2 subtype is abundant in the superficial laminae of the dorsal horn, where the M 4 subtype is expressed only at a low level (Duttaroy et al, 2002;Chen et al, 2005a (Chen et al, 2005a). The mAChRs, especially the M 2 subtype, are upregulated in the dorsal spinal cord in diabetic rats, which accounts for increased analgesic efficacy of mAChR agonists in diabetic neuropathic pain (Chen and Pan, 2003c). Upregulation of the M 2 subtype in small-and medium-sized DRG neurons has also been reported in rats with nerve injury-induced neuropathic pain (Hayashida et al, 2006).…”
Section: Distribution Of Machrs In Pain Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Using mAChR subtype knockout mice, it has been shown that the M 2 subtype is abundant in the superficial laminae of the dorsal horn, where the M 4 subtype is expressed only at a low level (Duttaroy et al, 2002;Chen et al, 2005a (Chen et al, 2005a). The mAChRs, especially the M 2 subtype, are upregulated in the dorsal spinal cord in diabetic rats, which accounts for increased analgesic efficacy of mAChR agonists in diabetic neuropathic pain (Chen and Pan, 2003c). Upregulation of the M 2 subtype in small-and medium-sized DRG neurons has also been reported in rats with nerve injury-induced neuropathic pain (Hayashida et al, 2006).…”
Section: Distribution Of Machrs In Pain Pathwaysmentioning
confidence: 99%
“…In this regard, blockade of mAChRs with atropine in the spinal cord causes a large decrease in the nociceptive threshold in rats (Zhuo and Gebhart, 1991). Intrathecal administration of mAChR agonists or acetylcholinesterase inhibitors produces a potent analgesic effect in rats, mice, and humans (Naguib and Yaksh, 1994;Hood et al, 1997;Ellis et al, 1999;Duttaroy et al, 2002;Chen and Pan, 2003c), and this analgesic effect is blocked by atropine (Naguib and Yaksh, 1994). The mAChRs also mediate some of the antinociceptive effects of opioids (Chen and Pan, 2001) and can enhance the analgesic effect of systemic opioids in humans (Hood et al, 1997).…”
Section: Antinociceptive Effect Of Machr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…A PE-10 catheter (8 cm) was inserted via a small opening made in the atlanto-occipital membrane of the cisterna magna such that the caudal tip reached the lumbar spinal enlargement (19). We then exteriorized the rostral end of the catheter and closed the wound with sutures.…”
Section: Methodsmentioning
confidence: 99%
“…To activate the device, a foot pedal was pressed to activate a motor that applied a constantly increasing force on a linear scale. When the animal displayed pain by either withdrawing of the paw or vocalizing, the pedal was immediately released, and the animal's nociceptive threshold was read on the scale (19).…”
Section: Methodsmentioning
confidence: 99%